Retrospective Analysis of the Formation of the Legal Base of Ukrainian-Polish Relations in Terms of Totalitarianism (1946 - second half of the 80th) - Horot, А.; Гороть, А. (Східноєвропейський національний університет імені Лесі Українки, 2016)
This article considers the peculiarities of the formation of the legal base of Ukrainian-Polish relations in terms of totalitarianism on the basis of retrospective analysis. It should be noted that the formation of diplomacy of this period did not always meet the established norms of international law in foreign relations, as contracting parties often resorted to radical (power) means of settling disputes. In this regulatory and legal system, the scheme of Ukrainian-Polish relations reproduced mainly formal contractual and legal process, the contents of which did not always meet the interests of both sides, but fully satisfied the ruling elite. As a result, relations between Ukraine and Poland had anextensive character. У статті на основі ретроспективного аналізу розглядаються особливості формування договірно-правової бази українсько-польських відносин в умовах тоталітаризму. Слід зауважити що формування дипломатії даного періоду не завжди відповідало усталеним нормам міжнародного права у зовнішніх зносинах, оскільки договірні сторони нерідко вдавалися до радикальних(силових) засобів вирішення спірних питань. У цій нормативно-правовій системі схема українсько-польських відносин відтворювала в основному формальний договірно-правовий процес, зміст якого не завжди відповідав інтересам обох сторін, але цілком задовільняв правлячу верхівку. Як наслідок, зв’язки між Україною і Польщею носили екстенсивний характер.
Ретроспективний аналіз формування договірно-правової бази українсько-польських відносин в умовах тоталітаризму(1946 – друга половина80-х рр.)
Keywords: diplomacy; contractual and legal base; bilateral cooperation; Poland; Soviet (Ukrainian)-Polish relations; Ukraine; дипломатія; договірно-правова база; двостороннє співробітництво; Польща; радянсько(українсько)-польські стосунки; Україна